Toxicity - Arianto, Budi; Khairunnisa, Khairunnisa; Aditama, Wiwit (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2024)
The dengue virus that causes dengue fever, which is very deadly, has not been resolved. The prevalence is very high. So far, the way to break the chain of transmission is to eradicate the vector. The chemical control applied causes many disadvantages, so the active ingredients of aloe vera extract can be used as a safer alternative to natural insecticides. This study aims to determine the difference in the concentration of Aloe vera extract as a larvicide. Experimental design with post test only control group design, sample of 600 instar III larvae, in 4 groups, 6 replications (negative control, 10% extract, 20% extract, 30% extract). Sample technique by purposive sampling method. The larvae were put in a test extract mixture of 100 ml. Observations were made 60 minutes after the treatment and the number of larval deaths was calculated. The percentage of larval mortality 60 minutes after treatment was 0% in control, 69.2% in 10% extract, 76% in 20% extract, 86.6% in 30% extract. Results were obtained with significant differences in the treatment groups. Aloe vera extract solution is a larvicide against Aedes aegyti.